Tuning the antimicrobial activity of microbial glycolipid biosurfactants through chemical modification - Pala, Melike; Castelein, Martijn G.; Dewaele, Camille; Roelants, Sophie L. K. W.; Soetaert, Wim K.; Stevens, Christian V. (Frontiers in Bioengineering and Biotechnology, 2024)
Sophorolipids, glycolipid biosurfactants derived from microorganisms such as Starmerella bombicola, possess distinctive surface-active and bioactive properties, holding potential applications in cosmetics, pharmaceuticals and bioremediation. However, the limited structural variability in wild-type sophorolipids restricts their properties and applications. To address this, metabolic engineering efforts have allowed to create a portfolio of molecules. In this study, we went one step further by chemically modifying microbially produced sophorosides, produced by an engineered Starmerella bombicola. Twenty-four new sophoroside derivatives were synthesized, including sophoroside amines with varying alkyl chain lengths (ethyl to octadecyl) on the nitrogen atom and their corresponding quaternary ammonium salts. Additionally, six different microbially produced glycolipid biosurfactants were hydrogenated to achieve fully saturated lipid tails. These derivatives, along with microbially produced glycolipids and three benchmark biosurfactants (di-rhamnolipids, alkyl polyglucosides, cocamidopropyl betaine), were assessed for antimicrobial activity against bacteria (Bacillus subtilis, Staphylococcus aureus, Listeria monocytogenes, Escherichia coli, Pseudomonas aeruginosa) and yeast (Candida albicans). Results indicated that microbially produced glycolipids, such as bola sophorosides, acidic sophorolipids and acidic glucolipids exhibit selective antimicrobial activity against the test organisms. Conversely, lactonic sophorolipids, sophoroside amines and quaternary ammonium salts display a broad antimicrobial activity. N-octyl, N-dodecyl and N-octadecyl derivatives exhibit the lowest minimal inhibitory concentrations, ranging from 0.014 to 20.0 mg mL-1. This study demonstrates the potential synergy of thoughtful biotechnology and targeted chemistry to precisely tailor glycolipid biosurfactants to meet specific requirements across applications.